Correction: Single-crystal TiO2 nanowires by seed assisted thermal oxidation of Ti foil: synthesis and photocatalytic properties. Issue 19 (13th February 2017) - Arcadipane, E.; Sanz, R.; Amiard, G.; Boninelli, S.; Impellizzeri, G.; Privitera, V.; Bonkerud, J.; Bhoodoo, C.; Vines, L.; Svensson, B. G.; Romano, L.
Abstract : Correction for 'Single-crystal TiO2 nanowires by seed assisted thermal oxidation of Ti foil: synthesis and photocatalytic properties' by E. Arcadipane et al., RSC Adv., 2016, 6, 55490–55498.